A Comparative Study on Demographic, Clinical and Laboratory Characteristics of Patients Undergoing Coronary Artery Bypass Graft in a Hospital in Iran: 2018-2019 and 2020-2021 - Parand pourghane; Maryam Ghalandari; Parinaz Shahroudi; Fatemeh Rahimi; Laleh Godarzwand (مجله دانشگاه علوم پزشکی گیلان)
Background Cardiovascular diseases are one of the most important causes of death and disability worldwide. The identification and prevention of risk factors and early treatment can prevent related mortality. Objective This study aims to compare the demographic, clinical, and laboratory characteristics of patients who underwent coronary artery bypass graft (CABG) surgery in a hospital in Rasht, Iran, in 2018-2019 and 2020-2021. Methods This cross-sectional study was conducted on patients who underwent CABG in Dr. Heshmat Hospital in Rasht. The study was divided into two time periods: 2018-2019 and 2020-2021, and the demographic, clinical, and laboratory characteristics of the patients and the surgery outcomes were compared between these two periods. The chi-square test, Fisher’s exact test, and Mann-Whitney U test were used to compare variables. Results The median age of patients was 60 years in 2018-2019 and 60.5 years in 2020-2021. In the first and second periods, patients’ body mass index (BMI) was 26.7 and 26.6 kg/m2, respectively. In the first period, 69.3% of patients were male, 57.7% were from urban areas and 43.5% were smokers. There were no significant differences in age, sex, BMI, smoking and place of residence of people between the two studied periods (P>0.05). Fasting blood sugar, low-density lipoprotein, triglycerides and cholesterol levels of patients were higher, and high-density lipoprotein was lower in the second period. The percentage of people with diabetes, ischemic heart disease, congestive heart failure, and myocardial infarction was lower in the first period, but the difference was not statistically significant (P>0.05). The mean diastolic blood pressure in the first period was lower, and a higher percentage of people had hyperlipidemia and hypertension in the second period, which were statistically significant (P<0.05). Conclusion By proper planning and holding stress control training classes and emphasizing continuous follow-up of health status and quitting smoking, the incidence or progress of heart diseases can be reduced to a great extent.